5-Benzylidene-2, 3-diarylthiazolidine-4-ones: Design, synthesis, spectroscopic characterization, in vitro biological and computational evaluation. Issue 17 (2nd September 2021) - Saeedian Moghadam, Ebrahim; Sameem, Bilqees; Abdel-Jalil, Raid; Faramarzi, Mohammad Ali; Amini, Mohsen
Abstract: The synthesis and antidiabetic activity of 5-Benzylidene-2, 3-diarylthiazolidine-4-one derivatives (6a–w ) are presented in the current work. Screening of derivatives 6a–w for their α-glucosidase inhibitory activity, showed higher inhibitory activity of twenty of the screened compounds (IC50 : 105–412 µM) in comparison to acarbose (IC50 : 750 µM) as a standard. Compounds 6r, 6b, and 6q exerted the best activity with the IC50 value of 105, 110, and 127 µM, respectively. Performing the kinetic studies, revealed the competitive mode of inhibition for 6r . It binds to the active site on the enzyme and competes with the substrate for binding to the active site. based on molecular docking studies, 6b, 6q, and 6r interact with HIS280, ASP307, and PRO312 residues, which show the important role of these residues inside the active site of the enzyme. Cytotoxicity studies also showed IC50 > 750 µM for 6a–w on different cell lines namely, NIH3T3, MCF-7, and HT-29. Graphical Abstract: UF0001